Clinical significance of preoperative and postoperative cytokeratin 19 messenger RNA level in peripheral blood of esophageal cancer patients. Issue 8 (18th September 2015) - Qiao, Y.‐F.; Chen, C.‐G.; Yue, J.; Ma, Z.; Yu, Z.‐T.
Summary: The purpose of this study is to analyze the correlation between preoperative/postoperative Cytokeratin 19 ( CK 19 ) messenger RNA (mRNA) level in peripheral blood (PB) and the clinical significance in esophageal cancer patients with different clinicopathological factors. We detected the preoperative and postoperative CK 19 mRNA level in the PB of 139 esophageal cancer patients who underwent complete resection and evaluated its clinical significance. We found that both the preoperative and postoperative CK 19 mRNA level increased in the esophageal cancer patients with lymph node metastasis, relapse or distant metastasis compared with that in cancers without lymph node metastasis, relapse or distant metastasis. High postoperative CK 19 mRNA levels indicate a short disease‐free survival (DFS) for the whole cohort esophageal cancer patients, whereas the high preoperative CK 19 mRNA levels only indicate a short DFS for the esophageal cancer patients with squamous cell carcinoma, TNM III stage, and lymph node metastasis. The dynamic change of CK 19 mRNA levels could indicate the prognosis of esophageal cancer patients. The patients with decreasing CK 19 mRNA level after surgery had good prognosis, and the patients with changeless CK 19 mRNA level had poor prognosis. Taken together, CK 19 mRNA levels could be a promising marker in assessing prognosis or assigning treatment for the esophageal cancer patients according to different clinicopathological factors.